2022
DOI: 10.1097/meg.0000000000002491
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasound pattern of hepatocellular carcinoma in noncirrhotic liver – results from the prospective multicentre DEGUM CEUS HCC study

Abstract: Objectives Contrast-enhanced ultrasound (CEUS) has a high diagnostic accuracy for the noninvasive diagnosis of hepatocellular carcinoma (HCC) in cirrhosis. However, as HCC in noncirrhosis becomes an emerging clinical concern, our study aimed to assess the diagnostic value of CEUS and the CEUS algorithms CEUS LI-RADS and ESCULAP in noncirrhotic liver in a prospective multicentre real-life setting. Methods High-risk patients for HCC with focal liver lesions upon B-mode ultrasound were recruited prospectively in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Patients usually present with larger nodule sizes, as they are not included in surveillance programs. The enhancement behavior in CEUS is similar to that in HCCs developed in the context of liver cirrhosis [34]. However, a multicenter study by Dong Y et al, including 96 patients, suggested that HCCs, developed in the non-cirrhotic liver, show arterial phase hyperenhancement with rapid washout [35].…”
Section: Discussionmentioning
confidence: 86%
“…Patients usually present with larger nodule sizes, as they are not included in surveillance programs. The enhancement behavior in CEUS is similar to that in HCCs developed in the context of liver cirrhosis [34]. However, a multicenter study by Dong Y et al, including 96 patients, suggested that HCCs, developed in the non-cirrhotic liver, show arterial phase hyperenhancement with rapid washout [35].…”
Section: Discussionmentioning
confidence: 86%